ANALYSIS OF CRACK FORMATION AND DEFORMABILITY OF BENT CONCRETE STRUCTURES REINFORCED WITH COMPOSITE REINFORCEMENT - Firsov, P.; Zolotov, S.; Nadtochii, S. (Municipal economy of cities. Series: «Economy science», 2023)
The scientific article is devoted to analysing the existing regulatory methods for calculating bending concrete structures reinforced with non-metallic composite reinforcement (FRP) according to deformations and crack formation (second group of limit states). It is known that FRP composite reinforcement does not behave in the same way as steel reinforcement, since, in many cases, their mechanical properties differ significantly. The existing foreign and Ukrainian norms and recommendations for calculating constructions with FRP reinforcement are mostly modifications of the norms for calculating reinforced concrete structures with steel reinforcement. The changes are mainly related to the rationing of the physical and mechanical properties of composite reinforcement and several empirical ratios. According to the recommendations of foreign standards, we considered the model of a beam with combined reinforcement (steel + GFRP) to carry out calculations for predicting the formation of cracks. The results of laboratory tests of an experimental beam with FRP reinforcement were compared with the results of theoretical calculations for predicting crack formation following the recommendations of the current foreign standards Eurocode 2 and ACI 440.1R-15. When comparing the results, it is clear that EC2 provides more approximate predictions of the cracking load than ACI. Deflections in the middle of the beam span from the moment of crack formation to the moment of destruction were determined. An experimental ‘load–deflection’ curve was constructed. The ratio between the experimental and predicted values of deflections using the EC2 and ACI methods was determined. According to the calculated data, both standards provide a sufficiently approximate forecast at 0,3Pult. The results of the research can be used in the future for the design of concrete structures reinforced with non-metallic composite reinforcement (based on glass fibres, basalt, carbon, aramid, etc.), however, further studies of structural elements working in bending under different load conditions and statistically justified confirmation are required.